An Analysis of Students Motivation in Off-Network-Based Creative Mathematics Learning - Imelda Imelda; Tetty Natalia Sipayung; Tatag Yuli Eko Siswono; Masriyah Masriyah (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
Mathematics learning during the COVID-19 pandemic was initially carried out online or based on a network (online). However, as time goes by where the spread of COVID-19 is getting smaller, mathematics learning is carried out face-to-face directly by paying attention to health protocols called offline or off-network-based learning. Therefore, teachers need to know the current student's learning motivation which is taught off-network-based learning. Therefore, an analysis of student motivation in off-network-based creative mathematics learning was carried out by giving a questionnaire to the seventh-grade students of SMP Dharma Wanita Medan, amounting to 27 people as research subjects. This research was conducted in the odd semester of the 2021/2022 Academic Year. While the object of this research is student learning motivation with six indicators, namely responsibility, trying to excel, liking challenges, independence, fortitude, and tenacity. This research is a qualitative-research with descriptive method. The results of this study stated that students' motivation in off-network-based creative mathematics learning was good.